Outbreak of clinical infectious laryngotracheitis in Turkey - Gulacti, I.; Eroksuz, Y.; Bulut, H.; Ceribasi, A. O. (British Veterinary Assoc, 2007)
[Abstract Not Available]
Keywords: Virus; Strains; Pcr